Structure of black aurora associated with pulsating aurora. Issue 11 (25th November 2015) - Fritz, Bruce A.; Lessard, Marc L.; Blandin, Matthew J.; Fernandes, Philip A.
Abstract: Morphological behavior of black aurora as it relates to pulsating aurora is investigated by examining a collection of ground‐based observations from January 2007 in support of the Rocket Observations of Pulsating Aurora rocket campaign. Images were sampled from video recorded by a Xybion intensified camera (30 fps) at Poker Flat Research Range, AK. The primary observations of black aurora recorded during the substorm recovery phase were between separate patches of pulsating aurora as well as pulsating aurora separated from diffuse aurora. In these observations the black aurora forms an apparent firm boundary between the auroral forms in a new behavior that is in contrast with previously reported observations. Also presented for the first time are black curls in conjunction with pulsating aurora. Curl structures that indicate shear plasma flows in the ionosphere may be used as a proxy for converging/diverging electric fields in and above the ionosphere. This new subset of black auroral behavior may provide visual evidence of black aurora as an ionospheric feedback mechanism as related to pulsating aurora. Key Points: Observations show new behavior of black aurora associated with pulsating aurora Black curls reported for the first time in conjunction with pulsating aurora New behavior a possible indicator of ionospheric feedback mechanism